BIAYA UTANG: PENGARUH GOOD CORPORATE GOVERNANCE DAN VOLUNTARY DISCLOSURE - Hairul Anam; Dika Karlinda Sari; Vino D (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2021)
The purpose of this study was to examine the effect of good corporate governance and voluntary disclosure on the cost of debt. The population of this research is 23 entities of Food and Beverages companies in Indonesia Stock Exchange. The research sample was purposive sampling method as many as 14 sample entities. This research analysis method uses multiple linear regression analysis techniques. The results showed that institutional ownership and voluntary disclosure had a significant effect on the cost of debt. Meanwhile, the independent commissioner and audit committee have no effect on the cost of debt.